Pengaruh Inflasi, Nilai Tukar Rupiah, dan Produk Domestik Bruto Terhadap Penerimaan PPN di Indonesia Periode 2005 – 2020 - Nadia Amelia; Tri Kunawangsih (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this study is to ascertain how GDP, inflation, and exchange rate affect VAT collection. Multiple linear regression or ordinary least squares is the research model used (OLS). The amount of VAT collected is the dependent variable in this study; the independent variables are inflation, exchange rate, and gross domestic product. The data in the time series is for example (2005-2020). Inflation, exchange rate, and inflation only have a small impact on VAT revenue, while GDP has a considerable positive impact.